2018
DOI: 10.1016/j.ecoleng.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Island topographies to reduce short-circuiting in stormwater detention ponds and treatment wetlands

Abstract: Island topographies to reduce short-circuiting in stormwater detention ponds and treatment wetlands The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters. Citation Balderas-Guzman, Celina et al. "Island topographies to reduce short-circuiting in stormwater detention ponds and treatment wetlands."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The effluent concentration was below 5 and 8 mg/L for TSS and BOD 5 , and higher removal efficiency was achieved for NH 4 -N (95%), NO 3 -N (77%), and phosphorus (DRP 65%) with at least 3-log E. coli removal (Park, Craggs, & Tanner, 2018). Guzman et al (2018) studied design considerations that improve hydraulic performance by reducing short-circuiting in detention pond and treatment wetland and concluded that a design with five rows of islands of decreasing size with distance from inlet would be effective in terms of hydraulic performance. studied the effect of DO on the nitrogen removal performance of single-stage biodegradable polymer-based CWs (PBSCW) while treating ammonia wastewater and reported that TN removal ratios in the PBSCW under limited-aeration and full-aeration phases were 72% and 99%, respectively, at an ammonia nitrogen loading rate of 25 g N/m 3 day.…”
Section: Wetland Design and Operationmentioning
confidence: 94%
“…The effluent concentration was below 5 and 8 mg/L for TSS and BOD 5 , and higher removal efficiency was achieved for NH 4 -N (95%), NO 3 -N (77%), and phosphorus (DRP 65%) with at least 3-log E. coli removal (Park, Craggs, & Tanner, 2018). Guzman et al (2018) studied design considerations that improve hydraulic performance by reducing short-circuiting in detention pond and treatment wetland and concluded that a design with five rows of islands of decreasing size with distance from inlet would be effective in terms of hydraulic performance. studied the effect of DO on the nitrogen removal performance of single-stage biodegradable polymer-based CWs (PBSCW) while treating ammonia wastewater and reported that TN removal ratios in the PBSCW under limited-aeration and full-aeration phases were 72% and 99%, respectively, at an ammonia nitrogen loading rate of 25 g N/m 3 day.…”
Section: Wetland Design and Operationmentioning
confidence: 94%
“…Shallow reservoirs are common hydraulic structures. They serve as storage or sedimentation tanks for stormwater management [1][2][3][4][5], and are part of green infrastructures such as constructed wetlands [6][7][8][9]. They are also used as settling basins in irrigation networks [10,11] and for the treatment of waste water [12] or drinking water [13].…”
Section: Context and Objectivementioning
confidence: 99%
“…A hydraulic efficiency value larger than 0.5 originated from a hydraulic modeling study of 13 hypothetical ponds to represent the influence of pond shape, inlet/outlet locations and types (Persson et al., 1999) and was adopted in Australian runoff quality research (Wong, 2006). Recently, laboratory simulations have been used to optimizing hydraulic efficiency for combinations of different lake shapes, inflow configurations, islands and obstacles (Guzman, Cohen, et al., 2018; Guzman, Nepf, et al., 2018).…”
Section: Habs and Global Constructed Waterbody Guidelinesmentioning
confidence: 99%